Penerapan Pendekatan Kontekstual dalam Pembelajaran Keterampilan Menulis Puisi pada Siswa Kelas X SMA PGRI 4 Kota Bogor - Sandi Budiana; Muhammad Nur Kamil (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2021)
This research aimed are to find out Contextual approach in Learning writing poetry and to find out the difficulties on students of X grade SMA PGRI 4 Bogor in writing poetry. Experiment method is used in this research. Data collection are test, questionnaire and observation. Students of X grade SMA PGRI 4 Bogor are population of this research. The sample of this research are experiment and controll class. Experiment treatment is X-2 grade IPA and Controll treatment is and X-1 IPA 2 . To get the data is obtained through Cluster random sampling. The first hyphothesis is implementation of Contextual Teaching and Learning (CTL) which increases writing poetry on students of X grade SMA PGRI 4 Bogor. It can proved based on the students’result of pretest and postest in experiment treatment is used Contextual Teaching and Learning (CTL) that is their improvement. Hyphotesis is students of X grade SMA PGRI 4 Bogor have barrier in writing poetry that is proved. Based on the result of students’ questionnare, they get barrier in writing poetry that is proved based on the 58,33% percentage, they difficult to choose words around 66,67%, then they difficult to choose vocabulary 66,67%, they use the proper and good words 66,67%, they conveys their feeling and idea to write poetry around 62,50%. Therefore, we concluded that Contextual Teaching and Learning (CTL) improves students to write poetry . Either they write poetry or they get barrier to write poetry.